Maxwell Zombies: Mulling and Mauling the Second Law of Thermodynamics - Sheehan, Daniel (Journal of Scientific Exploration, 2020)
Over the last decade two new classes of thermodynamic paradoxes have been investigated at the University of San Diego involving the recently identified phenomena of epicatalysis and supradegeneracy. These paradoxes add to a growing list of challenges to the second law of thermodynamics begun in the early 1990s. PACS numbers: 05.,05.70.Ce,05.20.-y Keywords: second law of thermodynamics; non-equilibrium; epicatalysis; supradegeneracy; statistical mechanics; laser; photovoltaics; thermophotovoltaics